All Hands-On Deck and All Decks on Hand: Surmounting Supply Chain Limitations During the COVID-19 Pandemic. (10th May 2021) - Warrington, Jill S.; Crothers, Jessica W.; Goodwin, Andrew; Coulombe, Linda; Hong, Tania; Bryan, Lynn; Wojewoda, Christina; Fung, Mark; Warrington, Gregory; Clark, Vanessa; Risley, Lauren; Lewis, Michael
Testing during the COVID-19 pandemic has been crucial to public health surveillance and clinical care. Supply chain constraints—spanning limitations in testing kits, reagents, pipet tips, and swabs availability—have challenged the ability to scale COVID-19 testing. During the early months, sample collection kits shortages constrained planned testing expansions. In response, the University of Vermont Medical Center, University of Vermont College of Medicine, Vermont Department of Health Laboratory, Aspenti Health, and providers across Vermont including 16 area hospitals partnered to surmount these barriers. The primary objectives were to increase supply availability and manage utilization. Within the first month of Vermont's stay-at-home order, the University of Vermont Medical Center laboratory partnered with College of Medicine to create in-house collection kits, producing 5000 per week. University of Vermont Medical Center reassigned 4 phlebotomists, laboratory educators, and other laboratory staff, who had reduced workloads, to participate (requiring a total of 5.3-7.6 full-time equivalent (FTE) during the period of study). By August, automation at a local commercial laboratory produced 22, 000 vials of media in one week (reducing the required personnel by 1.2 FTE). A multisite, cross-institutional approach was used to manage specimen collection kit utilization across Vermont. Hospital laboratory directors, managers, and providers agreed to order only as needed to avoid supply stockpiles and supported operational constraints through ongoing validations and kit assembly. Throughout this pandemic, Vermont has ranked highly in number of tests per million people, demonstrating the value of local collaboration to surmount obstacles during disease outbreaks and the importance of creative allocation of resources to address statewide needs.